2019
DOI: 10.25163/ahi.110006
|View full text |Cite
|
Sign up to set email alerts
|

Potential Malaysian medicinal plants for the treatment of Alzheimer’s disease

Abstract: Public interest statement Plants are rich source of chemical diversity and provides the initiation platform for any drug discovery programme. Identifying the potential plants with anti-cholinesterase activity provides a platform to develop more e ective drugs for treatment of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The effect of C. uvifera, M. elengi and S. aqueum extracts on motor, learning and memory function of POBCCA rats were evaluated in this study. Among the selected plant, M elengi and S. aqueum are common plants, while C. uvifera is an underutilised plant (Kumaran et al, 2019). No previous studies reported on the nootropic activity of the selected plant extracts except for the methanol extract of M. elengi leaves, which were reported to enhance memory in ageing and chemically induced dementia mice model (Joshi & Parle, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of C. uvifera, M. elengi and S. aqueum extracts on motor, learning and memory function of POBCCA rats were evaluated in this study. Among the selected plant, M elengi and S. aqueum are common plants, while C. uvifera is an underutilised plant (Kumaran et al, 2019). No previous studies reported on the nootropic activity of the selected plant extracts except for the methanol extract of M. elengi leaves, which were reported to enhance memory in ageing and chemically induced dementia mice model (Joshi & Parle, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Donepenzil, tacrine, galantamine and rivastigmine are the recommended acetylcholinesterase inhibitors [20] but few studies have warned that these drugs have extreme side effects i.e. hepatotoxicity and tremor are caused by tacrine and galantamine as well as weight loss, vomiting and diarrhea [21]. In this context, antiamnesic efficacy (in terms of percentage inhibition) of selected medicinal plants i.e.…”
Section: Acetylcholinesterase Inhibition Assaymentioning
confidence: 99%
“…The ten traditional Malaysian medicinal plants were Amaranthus spinosus L. Over the recent years, natural compounds derived from Malaysian medicinal plants have also received widespread attention as the main source of new therapeutic agents to treat neurological disorders and neurodegenerative diseases. The drugs prepared from plants are considered moderate in efficacy, less toxic and relatively low cost as compared to the commonly used pharmaceutical drugs (Kumaran et al 2019). Taken together, plants to cure disease and relieve physical suffering have been used by humans since their ancient times.…”
Section: Malaysian Herbsmentioning
confidence: 99%